Comparison between non-parametric indexes in the selection of biofortified curly lettuce - Peixoto, Joicy Vitória Miranda; Maciel, Gabriel Mascarenhas; Siquieroli, Ana Carolina Silva; Pereira, Lucas Medeiros; Luz, José Magno Queiroz; Marques, Douglas José (Comunicata Scientiae, 2020)
Selection indexes can be applied to simultaneous analysis of traits, increasing the efficiency of breeding in choosing the genotypes that meet the needs of both the market and the consumer. While it is a technic applied to several cultures, there are few studies about it in lettuce lines. For this reason, the aim of this study was to comparate assess the efficiency of different selection indexes for selecting biofortifiedleaf lettuce lines with good agronomic traits. The experiment was carried out at the Estação Experimental de Hortaliças of Federal University of Uberlândia (UFU), campus Monte Carmelo, in 2018. The experiment was designed in full randomized blocks of 3 repetitions with 25 leaf lettuce genotypes (22 lines from cultivars Pira 72 versus Uberlândia 10000 and 3 commercial cultivars – cv. Grand Rapids, UFU-Biofort and Uberlândia 10000). The lines are part of the UFU biofortified lettuce breeding program and were assessed for the total green mass (g), the stem diameter (cm), commercial leaves count, plant diameter (cm), foliar temperature (°C), SPAD index, anthocyanin content (mg 100g-1 sample), and bolting (days after sowing). To estimate selection gains, 10 genotypes were selected using both direct and indirect selection, as well as the traditional index, the sum of ranks index, Willians base index, and the multiplicative index. Mulamba and Mock sum of ranks index and Subandi multiplicative index provided the biggest total gains for the traits assessed in biofortified leaf lettuce. Both indexes were similar in selecting genotypes.